Pengaruh Work Life Balance dan Kepuasan Kerja Terhadap Kinerja Karyawan Pada PT. Kesawa Citra Integra - Suci Ayu Hardiyanti; Martinus Wahyu Purnomo (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
Kesawa Citra Integra is a company engaged in the sale of electronic goods such as aviation equipment, CCTV cameras, solar PV systems and Minearc Safety Systems. Does not produce goods directly but is an official distributor in Indonesia. This research aims to investigate the influence of 1) Work life balance on employee performance, 2) Job satisfaction on employee performance, and 3) Work life balance and job satisfaction on employee performance. This research took place in South Jakarta City using employees as research respondents. Multiple regression analysis was used to analyze data and evaluate the relationship between the independent variables (work life balance and job satisfaction) and the dependent variable (employee performance). Proving the research hypothesis uses multiple regression analysis techniques. The results obtained in this research 1) The research results show that work life balance and job satisfaction have a significant positive effect on employee performance. Managerial implications and suggestions for further research are discussed based on the findings of this study.